2014
DOI: 10.1517/14728222.2014.877891
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the Fc receptor in autoimmune disease

Abstract: Introduction The Fc receptors and their interaction with immunoglobulin and innate immune opsonins such as CRP are key players in humoral and cellular immune responses. As the effector mechanism for some therapeutic monoclonal antibodies and often a contributor to the pathogenesis and progression of autoimmunity, FcRs are promising targets for treating autoimmune diseases. Areas covered This review discusses the nature of different Fc receptors and the various mechanisms of their involvement in initiating an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 173 publications
(135 reference statements)
2
43
0
Order By: Relevance
“…We speculate that these increases were related to immune complex‐mediated inflammation (e.g. HS–IgG immune complexes), as described previously in other models . Further experiments are needed to confirm this hypothesis.…”
Section: Discussionsupporting
confidence: 80%
“…We speculate that these increases were related to immune complex‐mediated inflammation (e.g. HS–IgG immune complexes), as described previously in other models . Further experiments are needed to confirm this hypothesis.…”
Section: Discussionsupporting
confidence: 80%
“…A considerable FcRn binding affinity at high pH, such as the ABDEG variant, 16 limits the amount of FcRn molecules available for subsequent recycling, 43 and leads to the rapid degradation of the circulating antibodies, which is a concept used for a promising treatment of autoimmune diseases. 44,45 Furthermore, SELDEGs can selectively degrade antigenspecific antibodies through lysosomal degradation without affecting other host antibodies. 46 Although not within the scope of this study, variants identified here could have desired or improved properties for application in other types of disease treatment beyond antibody half-life extension.…”
Section: Discussionmentioning
confidence: 99%
“…Activating FcγRs on human (FcγRI/IIa/IIc/IIIa) and murine (FcγRI/III/IV) phagocytic cells contain ITAM motifs that recruit Syk and activate the PI3k pathway (12). Activation of FcγRs (FcγRI, III, and IV in mouse) is regulated by co-ligation with ITIM-containing inhibitory (FcγRIIB) receptors.…”
Section: Introductionmentioning
confidence: 99%